Design proposals for the preferred service ecosystem for senior citizens living at home: a service design study - Kattouw, Christophe Eward; Aase, Karina; Viksveen, Petter (Frontiers in Public Health, 2025)
IntroductionSignificant gaps exist between the preferred and the existing service ecosystem for senior citizens living at home emphasizing the need for transformation. This study aimed to develop design proposals for the preferred service ecosystem for senior citizens living at home.MethodsNine service design workshops were conducted with multiple stakeholder groups (n = 58), including senior citizens (aged 67 years or older), carers, health care professionals, municipal home care managers, municipal advisers, a bus driver, and representatives from the regional transportation provider. Stakeholders identified timely home care provision and age-friendly mobility as key areas for improvement. An inductive thematic analysis was applied to the workshop data.ResultsDesign proposals were developed including prototypes and design principles across seven domains: (1) enabling self-reliance; (2) housing and buildings; (3) urban mobility; (4) collaboration and education; (5) real-time communication; (6) resource organization and flexible scheduling; and (7) methods and tools to reshape patterns of thought. Design principles focused on enabling sufficient time and resources, improving accessibility, and changing mental models. These proposals may support senior citizens’ self-reliance, free up time and resources for service providers, and create time buffers for service delays.DiscussionThe design proposals demonstrate considerable interconnectedness and transferability across timely home care provision and age-friendly mobility. They may improve predictability and adaptive capacity for both senior citizens and service providers.